Lower esophageal membrane: about an operated case - Praderi, Luis; Vega, Dardo (Cirugía del Uruguay, 2020)
a 25-year old patient with a history of dysphagic episodes from the age of 4, is reported. A brief survey of this infrequent conditions is made. Distinctive features with ectopic cardia and stenosis from esophagitis, are dealt with. The case under consideration underwent surgical resection, followed by thorough cure. Endoscopy during surgery, as a useful means of locating the lesion, is advocated. We are concerned with the furst case reported in this country and the third one in the world bibliography, treated through esophagotomy and resection.